Maternal and fetal out come in meconium stained amniotic fluid in a tertiary centre - Unnisa, Sadiq; B.S., Sowmya; Rao, Smitha B.; K., Rajagopal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was undertaken to determine the correlation of amniotic fluid stained with meconium (MSAF) with maternal and fetal outcome. Methods: This prospective observational study was carried out in the Department of obstetrics and gynecology, Yenepoya medical college, Mangalore over a period of 14 months between January 2013 to march 2014. A total of 1000 pregnant women who had completed more than 37weeks of gestation with singleton pregnancies & cephalic presentation were included in this study. MSAF on spontaneous or artificial rupture of membranes were monitored during labour with fetal heart rate abnormality, consistency of liquor, 1 minute and 5 minute Apgar score, LSCS, instrumental delivery, NICU admissions and neonatal complications as outcome variables. Results: Women were divided into two groups: 350 women with MSAF as cases, while 650 women with clear liquor were taken as controls. Among 350 cases with MSAF, 70 % were unbooked and 30 % were booked pts. About 75.7% of women were between 20-30 years of age-group. Primi gravidas constituted 51.4% in study group. Approximately 41.4% cases had gestational ages of 39 -39+6. Among MSAF 55.4% were thin stained & 44.5%were thickly stained. 45.7% showed fetal heart abnormalities on electronic monitoring & presence of fetal bradycardia was higher. Caesarean section rates were nearly triple in cases (45.7% vs 15.7%). Fetal out come in regard to Apgar score at birth, birth asphyxia, MAS, increased NICU admissions were more in cases. Incidence of Male to female was high (52.6% vs 47.3%). Conclusions: Presence of MSAF is worrisome for both the obstetrician and pediatricians view as it increases surgical intervention, birth asphyxia, MAS & NICU admissions.